1979
DOI: 10.1111/j.1346-8138.1979.tb01920.x
|View full text |Cite
|
Sign up to set email alerts
|

Plaque Type Syringoma

Abstract: Special types of syringoma include eruptive syringoma (1) and syringoma on the vulva and on the upper extremities (2). We present a large one, 1×5 cm in size, found on the right side of the neck, and preoperatively diagnosed as nevus sebaceus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
2
3

Year Published

1986
1986
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 3 publications
1
13
2
3
Order By: Relevance
“…Localized syringomas with unusual clinical features include cases developing in rare areas such as the genitalia, neck, or trunk and those showing a unilateral linear distribution or plaque formation (1)(2)(3)(4)(5). Kikuchi et al (1) first reported a case of plaque type syringoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Localized syringomas with unusual clinical features include cases developing in rare areas such as the genitalia, neck, or trunk and those showing a unilateral linear distribution or plaque formation (1)(2)(3)(4)(5). Kikuchi et al (1) first reported a case of plaque type syringoma.…”
Section: Discussionmentioning
confidence: 99%
“…Occasionally, other areas, including the anterior chest, trunk, neck, and external genitalia, are also affected (1)(2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…An uncommon plaque type has also been described. 26 First described in 1872 by BiesiadeckiZ7 and Kaposi," and called lymphangioma tuberosum multiplex, these tumors are histologically composed of small ductal structures lined by two rows of epithelial cells. These ducts lie within a fibrous dermal stroma and may become elongate and take the shape of a tadpole or comma.…”
Section: Introductionmentioning
confidence: 99%
“…This is an uncommon variant that may easily be misdiagnosed as MAC 9 . This rare type of syringoma was first described in 1979 by Kikuchi et al 10 A total of nine cases have been reported, most of them localized on the neck or face, the onset ranging from 6 to 78 years. Clinically, solitary brownish lichenoid plaques about 1 to 7 cm in size have been described.…”
Section: Discussionmentioning
confidence: 99%